Analysis of Stress Level Through the Influence of Organizational Culture, Servant Leadership, Personality on PT. Employees XYZ - E. Sudarmi; Susi Adiawaty; Encep Rahmat Selamet (Future Science, 2023)
This study aims to determine the influence of organizational culture, servant leadership and personality on employees' work stress (case study of XYZ branch employees). In this research method, the population consists of the employees of Store XYZ. The sample size used was 103 respondents. Data processing analysis uses the associative method. The sampling technique used was saturated sampling. Data analysis methods use validity tests, reliability tests, multiple regression, F-test and t-test. The results of the research show that from the four hypotheses proposed in this research it can be states that organizational culture influences employees and service providers management towards employees, work stress has and continues to have an impact on employees Corporate culture, servant leadership.